PENGARUH EFEKTIVITAS SISTEM AKUNTANSI KEUANGAN DAERAH DAN SISTEM PENGENDALIAN INTERN TERHADAP KUALITAS AKUNTABILITAS KEUANGAN - B2092162001, ARIEF KURNIAWAN (MAKSI UNTAN, 2019)
This study is specifically concerned with the empiric proof of the effectiveness of Regional Financial Accounting System and Intern Management System toward the quality of financial accountability. The research form being used was hypotheses testing, which explains the phenomenon in the forms of relationship between variables. The population was taken from Regional Work Unit of Kubu Raya that was involved in the reconstruction of design and usage of Regional Financial Accounting System. They were the head service/council/office/sub-district head and the expenditure treasurer. Samples of this research consisted of the head service/council/office/sub-district head and the expenditure treasurer on Regional Work Unit of Kubu Raya. The analysis instrument was Statistical Product and Service Solution (SPSS) version 25.00 with simplified and multiplied regression analysis. The result showed that overall hypothesis is accepted. The effectiveness of Regional Financial Accounting System and Intern Management System are provenly impactful to the quality of financial accountability.Â Keywords: The Effectiveness of Regional Financial Accounting System, Intern Management System, quality of financial accountability.